Education in developing countries: issues, trends, and assessment of policies - Glewwe, Paul (Henry Stewart Talks, 2016)
Economic analysis of education, Public/Private costs and benefits, Trends in education, Big increases in enrollment, Low learning outcomes in developing countries, Policies that increase time in school, Policies that increase student learning, Why a policy “does/does not work”